Syntactic Analysis of Serial Verb Constructions in Arabic Language - Nurainun Hasibuan; Mulyadi Mulyadi (Randwick International of Education and Linguistics Science Journal, 2024)
This research discusses Serial Verb Constructions found in both written and spoken Arabic language. The study is conducted using Syntax Analysis, employing a qualitative descriptive research design. Data collection is done through document analysis and fieldwork by collaborating techniques of reading, listening, and note-taking. Data sources are obtained in two forms, written data sourced from the Quran, and field data acquired from conversations with students at Darularafah Islamic boarding school. The data analysis stage employs the method proposed by Sudaryanto (2015:15), which emphasizes language analysis tools derived from the language itself, delineated in basic techniques only. This research aims to classify the Serial Verb Constructions in the syntactic formation of Arabic language based on the relationship between the first verb (V1) and the second verb (V2). The findings show that there are patterns in forming serial verbs in Arabic, such as V1 + V2 Pattern, V1 + the letter أن /an/ + V2 Pattern, V1 + the letter /lan/ + the letter أن /an/ + V2 Pattern, إن /in/ + V1 + V2 Pattern, لم /lam/ + V1 + V2 Pattern, and كَيْفَمَا /kayfama/ + V1 + V2 Pattern.